1985
DOI: 10.1111/j.1751-1097.1985.tb03540.x
|View full text |Cite
|
Sign up to set email alerts
|

SPECTROSCOPIC STUDIES OF CUTANEOUS PHOTOSENSITIZING AGENTS–VIII. A SPIN‐TRAPPING STUDY OF LIGHT INDUCED FREE RADICALS FROM CHLORPROMAZINE and PROMAZINE

Abstract: Abstract— The clinically important phenothiazine drugs, particularly chlorpromazine, often elicit phototoxic and photoallergic reactions. We have used the spin traps 2‐methyl‐2‐nitrosopropane (MNP) and 5,5‐dimethyl‐pyrroline‐N‐oxide (DMPO) to define the radical photolysis pathways of chlorpromazine and promazine. In the absence of oxygen the dechlorination product of chlorpromazine is trapped by MNP. The reactivity of the dechlorination product is similar to that of the phenyl radical as shown by its ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 25 publications
7
38
0
Order By: Relevance
“…SI-5), therefore being a possible photoproduct precursor of 317 m/z. In another study, excitation with wavelengths ≥330 nm was shown to produce 2-hyxdroxypromazine as well as CPR sulfoxide, whereas only irradiation under UVB exposure (≤270 nm) led to the formation of the CPR cation radical and therefore possibly hydroxylated CPR derivates [56]. These findings correlate well with the results of our study, as the xenon lamps' emission spectrum ranges from 300 nm to 800 nm.…”
Section: Discussionsupporting
confidence: 91%
“…SI-5), therefore being a possible photoproduct precursor of 317 m/z. In another study, excitation with wavelengths ≥330 nm was shown to produce 2-hyxdroxypromazine as well as CPR sulfoxide, whereas only irradiation under UVB exposure (≤270 nm) led to the formation of the CPR cation radical and therefore possibly hydroxylated CPR derivates [56]. These findings correlate well with the results of our study, as the xenon lamps' emission spectrum ranges from 300 nm to 800 nm.…”
Section: Discussionsupporting
confidence: 91%
“…Computer simulation of this EPR spectrum indicates that the spin adduct corresponds to a carbon-centered radical with hyperfine splittings a N = 16.1 G, α H = 23.6 G, NoH = 0.68, where NoH is the ratio of the nitrogen splitting constant to the hydrogen splitting constant (NoH = a N /a H ). 47 The similarity of this adduct and the previously reported 2-chlorophenyl-DMPO adduct (a N = 15.8 G, α H = 23.8 G, NoH = 0.65) 48 suggested that it was formed by reaction of the spin trap with an aryl radical generated during the photochemical reaction of 2,6-DBP. EPR spin trapping experiments with DMPO demonstrated that high levels of keto radical were produced during the irradiation of 2,6-DBP (Figure 5).…”
Section: Resultssupporting
confidence: 76%
“…Recent spin-trapping studies by Motten et al (9) have confirmed that superoxide is indeed generated during the irradiation of aqueous solutions of promazine. While the DMPO-hydroxyl radical adduct has been observed during the photoirradiation of chlorpromazine, promazine, triflupromazine, and methoxypromazine (9,11) it seems unlikely that the hydroxyl radical is a primary photoproduct and therefore this reactive species cannot be involved in the phototoxicity of these drugs.…”
Section: Chlorination Of Chlorpromazine and Prochlorperazine In Methamentioning
confidence: 79%